Natural dye-sensitized solar cell based on nanocrystalline TiO2 - Khalil Ebrahim Jasim, (Universiti Kebangsaan Malaysia, 2012)
During the last quarter of the twentieth century there have been intensive research activities looking for green sources of energy. The main aim of the green generators or converters of energy is to replace the conventional (fossil) energy sources, hence reducing further accumulation of the green house gasses GHGs. Conventional silicon and III-V semiconductor solar cell based on crystalline bulk, quantum well and quantum dots structure or amorphous and thin film structures provided a feasible solution. However, natural dye sensitized solar cells NDSSC are a promising class of photovoltaic cells with the capability of generating green energy at low production cost since no vacuum systems or expensive equipment are required in their fabrication. Also, natural dyes are abundant, easily extracted and safe materials. In NDSSC, once dye molecules exposed to light they become oxidized and transfer electrons to a nanostructured layer of wide bandgap semiconductors such as TiO2. The generated electrons are drawn outside the cell through ohmic contact to a load. In this paper we review the structure and operation principles of the dye sensitized solar cell DSSC. We discuss preparation procedures, optical and electrical characterization of the NDSSC using local dyes extracted from Henna (Lawsonia inermis L.), pomegranate, cherries and Bahraini raspberries (Rubus spp.). These natural organic dyes are potential candidates to replace some of the man-made dyes used as sensitizer in many commercialized photoelectrochemical cells. Factors limiting the operation of the DSSC are discussed. NDSSCs are expected to be a favored choice in the building-integrated photovoltaics (BIPV) due to their robustness, therefore, requiring no special shielding from natural events such as tree strikes or hails.